Kinetics and mechanism of the Cl-initiated oxidation of 4-tert-butylcyclohexanone at atmospheric conditions: Reactivity, SARs and fate of the alkoxy radicals formed. (1st February 2023) - Baptista, Andrea; Blanco, María B.; Gibilisco, Rodrigo G.; Teruel, Mariano A.
Abstract: The rate coefficient of the gas-phase reaction of 4-tert-butylcyclohexanone (4-TBCH) with Cl atoms was determined by the relative method in a Teflon collapsible chamber with GC-FID detection to be k 4-TBCH = (2.84 ± 0.40) × 10 −10 and in a glass photoreactor with in situ FT-IR detection to be k 4-TBCH = (2.74 ± 0.64) × 10 −10 . As an average value of the GC-FID and FT-IR techniques, it is recommended k 4-TBCH = (2.79 ± 0.34) × 10 −10 (all values in cm 3 molecule −1 s −1 ) at 298 K and 760 Torr. Reactivity trends were developed with respect to the nature and position of the substituents in the cycle of the Volatile Organic Compounds (VOCs) compared. On the other hand, Structure Activity Relationship (SAR) were performed and compared with the kinetic data obtained in the present work and used to predict the more favorable site of H abstraction in the cyclic ketone. In addition, the products formed under atmospheric conditions were identified for the first time by SPME/GC-MS and FT-IR detection. Acetone, formaldehyde, pivalaldehyde, pivalic acid and a chlorinated alkane were the main products identified. The tropospheric lifetimes of 4-TBCH were calculated from the rate coefficients determined for this cyclic ketone, indicating that the main degradation pathway will be the reaction with OH radicals with a local impact, where Cl atoms could be a significant sink of this ketone in coastal areas. In this sense, the tropospheric ozone creation potential of 4-TBCH and their photooxidation products were determined. The ketone studied 4-TBCH and the 1, 4-cyclohexanedione identified as a product are the major ozone producers and other oxygenated products as formaldehyde or pivalaldehyde, showed a moderate photochemical smog production. Graphical abstract: Image 1 Highlights: Reactivity increases with alkyl substitution in cyclic ketones. Carbonyl deactivates the (α)-positions for H abstraction. (β)- (γ)-positions favored to H abstraction by SAR calculations. Pivalaldehyde and pivalic acid produced by ring opening. 1, 4-cyclohexanedione generated by keeping the ketone cycle during oxidation.